Chinese herbal medicines: the modifier of hepatocellular carcinoma targeting Wnt/β-catenin signaling pathway - Zhang, Yifan; Li, Hongkun; Jiang, Na; Ru, Qingjing (Frontiers in Pharmacology, 2025)
Hepatocellular carcinoma (HCC) is a prevalent malignant neoplasm of the digestive system, including 80% of primary liver malignancies. The Wnt/β-catenin signaling pathway plays a key role in immune response and tumer resistance. A growing number of studies have shown that the Wnt/β-catenin signaling pathway is involved in the pathogenesis of HCC. The Wnt/β-catenin pathway affects HCC in a variety of ways, including by influencing gene mutations, regulating dendritic cells, T-cells, and tumor cells, and influencing tumer resistance. Presently, conventional chemotherapy exhibits several drawbacks, including side effects, restrictions, and the emergence of tumer resistance. Traditional Chinese medicine (TCM) are characterized by multiple actions, multiple targets, few side effects, and improved immunity, and their combination with common clinical therapies can prolong patient survival and reduce postoperative recurrence rates, providing a new idea of combination therapy for the alleviation and improvement of HCC. This review focuses on TCM as an adjunct to surgery, targeted therapy, interventional therapy to improve the HCC microenvironment, reverse tumer resistance, and reduce treatment side effects by modulating the Wnt signaling pathway. It should be clear that TCM should not replace the first-line treatment plan of modern medicine, and its core value is to improve the comprehensive efficacy and quality of life of patients. This research examines the role of the Wnt/β-catenin signalling system in developing HCC and describes how TCM and plant active metabolites, crude extracts of single botanical drugs and Chinese herbal formulations affect the progression of HCC by modulating different targets of the Wnt/β-catenin signalling pathway or by modulating other pathways related to the Wnt/β-catenin signalling pathway. This review is intended to provide new ideas and options for the prevention and treatment of HCC.